Social equity and sustainability considerations in the planning of Nature-based solutions in Southern African Water Towers - Campbell, Andrea (Department of Environmental and Geographical Science, 2023)
Nature-based solutions (NbS) – ecosystem protection, restoration, sustainable management, and creation – are increasingly being promoted to support human well-being and ecosystem health, particularly in the context of a changing climate. As such, NbS are gaining popularity globally in international policy and programmes resulting in an increase in multilateral funding from the Global North for NbS projects in developing countries. However, concerns have arisen around how suitable these interventions are in local contexts where local communities are heavily reliant on natural resources given the potential for social, economic, and environmental trade-offs. This research aimed to address these concerns by exploring: i) whether and how social equity has been considered in NbS project design, particularly in relation to vulnerable groups; and ii) whether project sustainability (in terms of longevity and more broadly in terms of sustainable development) has been linked to social equity. The research focused on Southern African NbS projects that are of relevance to areas important to water supply (known as Water Towers). This excluded all marine, coastal, and urban NbS types. Firstly, a systematic mapping was undertaken of relevant multilateral funded project documents (number of projects=134) for the region. Secondly an in-depth qualitative analysis of project planning documents for a random subset (np=16) of these latter NbS projects was conducted using a multidimensional equity framework, including distributional, procedural, and recognitional dimensions of equity. Research findings show that NbS projects in Southern Africa tend to incorporate multiple NbS types into individual country projects targeting cross-cutting societal challenges including climate change adaptation, food security, sustainable livelihoods, and conservation among others. While distributional and procedural equity aspects were mentioned in the project documents, there was a lack of clear details showing how these equity considerations would be supported and realised in project implementation. Recognitional equity, despite being mentioned with a focus on details of the inclusion of traditional and indigenous knowledge was generally excluded from NbS project design. While gender was regularly broadly considered, there was limited evidence of attempts to differentiate vulnerable groups within local communities. Project sustainability was somewhat linked to social equity in project design through regular mention of capacity building and participation in the project documentation, but large gaps existed, particularly in relation to the processes of local-level participation. Furthermore, projects did not fully recognise the complexity inherent in working towards multiple, at times conflicting, goals related to sustainable development when considering achieving equity in local contexts, e.g., where local natural resource management and agricultural practices were at odds with the project related NbS objectives. This is an example of a type of constraint to achieving social equity in NbS that should be considered and addressed during NbS design and planning. This research echoes calls for equitable approaches to NbS design and planning that recognise that social equity should be both a process and an outcome of NbS to contribute towards sustainable development. For this to be achieved multidimensions of equity need to be incorporated early in the design and planning of NbS, and through to implementation.